The Role of Country Perceived Image And Review of Beauty Vlogger on Consumer Purchase Intention of Cosmetic Products - Luh Komang Candra Dewi; Ni Luh Kardini; Yunidyawati Azlina; Tengku Kespandiar; Eka Kurnia Saputra (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to analyze the effect of country image and beauty vlogger reviews on purchase intention, analyze whether beauty vlogger reviews have an effect on purchase intention and analyze whether country image and beauty vlogger reviews have an effect on purchase intention. This research will be conducted to analyze the effect of country image and Beauty vlogger review on Purchase Intention of Korean cosmetics consumers on the Althea.kr website. The survey will be shared via the comments column on Veronica Ong's video channel. Using a web survey via Google form. In recent years, web surveys have been used to collect respondent data for academic research as well as authors sharing surveys online on forums discussing the Althea.kr site, researchers posting survey messages in the comments column by providing a link to beauty vlogger Veronica Ong's video. The conclusion from this study is that country image has a significant effect on purchase intention, beauty vlogger reviews have a significant effect on purchase intention and together country image and beauty vlogger review have a significant effect on purchase intention of Korean cosmetic products. In terms of country image, in this study country image shows significant results on the purchase intention of cosmetic products from South Korea. Here Althea.kr has described products from South Korea and reflects the characteristics of South Korea as a developed country in the field of cosmetics.